Moral rules and moral ideals: A useful distinction in business and professional practice - Hennessey, John W. (Journal of business ethics, 1985)
The distinction between moral rules and moral ideals is presented and explained in various ways. The authors propose that people in business are required to obey the moral rules and have a choice with respect to ideals. Thus, they are not in a different position from that of anyone else in society., Four case studies are presented and discussed. The analytical approaches used by the authors' students are summarized and evaluated. The moral rules/ideals paradigm is described as helping discussants of the cases to establish congruence between business ethics and their personal set of values. Other values of the classroom discussion of ethics cases are considered.